Effective flexural rigidity for interaction diagram of slender reinforced concrete columns exposed to fire. (December 2022) - Kim, Han-Soo
Abstract: A method for obtaining the interaction diagrams of slender reinforced columns exposed to fire was developed, which employed mathematical optimization to obtain the maximum stress resultants and corresponding strain parameters of a concrete section. Flexural rigidity is defined as the maximum bending moment at balanced failure divided by the corresponding curvature. The second-order effect for the columns subjected to biaxial bending was considered with two flexural rigidities about the strong and weak axes. A scale factor of 2 for the effective flexural rigidity was recommended after comparing the fire resistances of the 74 experimental columns. The interaction diagrams of a rectangular reinforced concrete column are presented here to demonstrate the usefulness of the proposed method.